2021
DOI: 10.1186/s12872-021-02364-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement associated infective endocarditis case series: broadening the criteria for diagnosis is the need of the hour

Abstract: Background Transcatheter valve replacement (TAVR) is an important therapeutic intervention for patients with aortic valve stenosis. As TAVR has become available to a broader population, there has been an increase in the number of less common, yet potentially catastrophic, complications. TAVR related infective endocarditis (TAVR-IE) is a rare, but potentially fatal, complication. Case series We present here two patients that we encountered for TAVR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In view of the expanding number of TAVR procedures, rare complications including infective endocarditis have been reported. Complications may manifest as catastrophic aortic root dissection, paravalvular and aortic root abscesses, and intra/paravalvular regurgitation (5). Studies have estimated that the 1-year incidence of prosthetic valve endocarditis (PVE) complicating TAVR (TAVR-PVE) ranges between 0.2% (in the PARTNER 3 trial) and 3.1% (in a Danish cohort study including 509 patients) (4,6).…”
Section: Of 17mentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the expanding number of TAVR procedures, rare complications including infective endocarditis have been reported. Complications may manifest as catastrophic aortic root dissection, paravalvular and aortic root abscesses, and intra/paravalvular regurgitation (5). Studies have estimated that the 1-year incidence of prosthetic valve endocarditis (PVE) complicating TAVR (TAVR-PVE) ranges between 0.2% (in the PARTNER 3 trial) and 3.1% (in a Danish cohort study including 509 patients) (4,6).…”
Section: Of 17mentioning
confidence: 99%
“…The diagnosis of TAVR-PVE may be challenging due to the low sensitivity of conventional diagnostic tools and the panoply of non-specific symptoms (5). In light of its high mortality and dreadful complications, clinicians should have a low threshold to consider PVE in patients with a history of TAVR who present with suggestive symptoms and signs to promptly initiate proper management.…”
Section: Of 17mentioning
confidence: 99%
“…One of the specific conditions that poses a challenge on the sensitivity of the modified Duke criteria in general and on echocardiography specifically is TAVI-IE. The decreased sensitivity of echocardiography is a attributed to the location of vegetation and the acoustic shadow of the valve stent [24][25][26]. Recently, a few reports have suggested that FDG PET/CT in this setting can contribute to improved diagnosis [27,28].…”
Section: Fdg Pet/ct In Tavi-iementioning
confidence: 99%
“…In view of the expanding number of TAVR procedures, rare complications including infective endocarditis have been reported. Complications may manifest as catastrophic aortic root dissection, paravalvular and aortic root abscesses, and intra/paravalvular regurgitation [ 5 ]. Studies have estimated that the 1-year incidence of prosthetic valve endocarditis (PVE) complicating TAVR (TAVR-PVE) ranges between 0.2% (in the PARTNER 3 trial) and 3.1% (in a Danish cohort including 509 patients) [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of TAVR-PVE may be challenging due to the low sensitivity of conventional diagnostic tools and the panoply of non-specific symptoms [ 5 ]. In light of its high mortality and dreadful complications, clinicians should have a low threshold to consider TAVR-PVE in patients who present with suggestive symptoms and signs and should initiate prompt management.…”
Section: Introductionmentioning
confidence: 99%